Frequency of Multiple Gestations in Kohat - Ramzan, Muhammad; Yasmeen, Fauzia; Afzal, Shazia; Ghani, Shahida; Mahmood, Shahid; Syeda, Bibi; ., Rafia (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine the frequency of multiple gestations in Kohat City.Study Design: Retrospective longitudinal study.Place and Duration of Study: Labour Room and Neonatal Intensive Care Unit (NICU), Combined Military Hospital, Kohat Pakistan, from Jan 2019 to Dec 2020.Methodology: We included 5285 women delivered at Combined Military Hospital, Kohat Pakistan, during our study period.Basic data were collected from medical record files, and further information was gathered through telephonic interviews with the patients. The frequency of multiple gestations was calculated and compared with local and international statistics.Results: Out of 5285 deliveries during the study period, there were significant twin pregnancies 156(2.95%) and triplet pregnancies 11(0.21%). 167(3.16%) multiple deliveries were managed at our centre. Further probing showed that 109(65.3%) women used induction medication from registered medical practitioners or quakes/ spiritual healers to get pregnant.Conclusions: Multiple gestations and the use of induction therapy are much higher in Kohat compared to other parts of the country.